Compact embedded device for lock-in measurements and experiment active control - Luda, Marcelo Alejandro (2019)
We present a multi-purpose toolkit for digital processing, acquisition, and feedback control designed for physics labs. The kit provides in a compact device the functionalities of several instruments: function generator, oscilloscope, lock-in amplifier, proportional-integral-derivative filters, ramp scan generator, and a lock-control. The design combines field-programmablegate-array processing and microprocessor programing to get precision, ease of use, and versatility. It can be remotely operated through the network with different levels of control: from simple off-the-shelf Web graphical user interface to remote script control or in-device programmed operation. Three example applications are presented in this work on laser spectroscopy and laser locking experiments. The examples include side-fringe locking, peak locking through lock-in demodulation, and complete in-device Pound–Drever–Hall modulation and demodulation at 31.25 MHz and advanced acquisition examples like real-time data streaming for remote storage.